ANALISA PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN (Studi Pada PT. Berkat Manunggal Jaya di Semarang) - Burhanuddin Nashrul, 12.05.51.0197 (Students Journal of Economic and Management, 2016)
Human resources play an important role in a company since human is the power and determiner of the organization. Todayâs business needs a high performance of the human resources in order to develop their company. Logically, by improving the quality, the performance of the employees will be higher. This research was conducted in PT. Berkat Manunggal Jaya Semarang. The goal of this research is to determine the effect of leadership style, working environment and compensation toward employeeâs performance. The leadership style, working environment and compensation are the independent variables on this research, whereas the employeeâs performance played as the dependent variable. The population of the study was the 100 employees of PT. Berkat Manunggal Jaya Semarang. Census study was used as the sampling technique this research. The data were analyzed by multiple linear regression analysis method supported by SPSS program. The results of this study indicate that the style of leadership and compensation significantly influence employee performance in PT. Berkat Manunggal Jaya Semarang with positive direction. While working environment but not significant effect on employee performance. Keywords: Leadership style, Working environment, Compensation and Performance Employeeâs